2022
DOI: 10.1021/acs.chemmater.2c01941
|View full text |Cite
|
Sign up to set email alerts
|

When Design Meets Function: The Prodigious Role of Surface Ligands in Regulating Nanoparticle Chemistry

Abstract: The underlying power of "interplay of forces" in controlling the properties and functions at the nanoscale is highlighted in this perspective. This interplay is achieved by installing attractive and repulsive forces, via proper ligand chemistry, which will guide the nanomaterials to interact with their surroundings as per the need. Along with improving the existing properties, the balancing of attractive and repulsive forces holds the prospects of imparting newer functions as well. The concept of "ligand-direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 162 publications
0
31
0
Order By: Relevance
“…A widely used electron mediator, [Cp*Rh(bpy)(H 2 O)] 2+ , was incorporated to enhance the charge transfer rate for a better comparison of the reaction yields under different excitations as well as to regenerate the enzymatically active 1,4-NADH. 43−45 Moreover, the incorporation of a positively charged electron mediator allowed us to use electrostatic forces as a tool to install the concept of "catalyst−reactant interaction" 11,12,46 in our study. A favorable catalyst−reactant interaction will channelize the diffusion and increase the local concentration of the reactants close to the surface of the catalyst, thereby enhancing the possibility of the charge transfer process.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A widely used electron mediator, [Cp*Rh(bpy)(H 2 O)] 2+ , was incorporated to enhance the charge transfer rate for a better comparison of the reaction yields under different excitations as well as to regenerate the enzymatically active 1,4-NADH. 43−45 Moreover, the incorporation of a positively charged electron mediator allowed us to use electrostatic forces as a tool to install the concept of "catalyst−reactant interaction" 11,12,46 in our study. A favorable catalyst−reactant interaction will channelize the diffusion and increase the local concentration of the reactants close to the surface of the catalyst, thereby enhancing the possibility of the charge transfer process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A favorable catalyst−reactant interaction will channelize the diffusion and increase the local concentration of the reactants close to the surface of the catalyst, thereby enhancing the possibility of the charge transfer process. 11,12,46 Accordingly, the surface of the AuNRs was appropriately functionalized with negatively charged ligands to achieve electrostatic attraction with the positively charged electron mediator. Detailed wavelengthdependent experiments showed that hot charge carriers generated through selective interband transitions (via excitation at ∼450 nm) yielded the best photocatalytic regeneration of the NADH cofactor, compared to selective intraband (via excitation at ∼808 nm) and inter + intraband transitions (via excitation at ∼532 nm).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve this, different strategies have been explored, including the use of: surfactants and micellar catalysis, various supports (with different metal-support interactions) or organic ligands. 1 Although the latter strategy was initially achieved through the use of ligands such as thiols, amines, cyanides, disulfides, thioethers or phosphines, 2 N-heterocyclic carbene (NHC) ligands, which are now privileged ligands in organometallic chemistry and homogeneous catalysis, have been established as novel promising stabilisation agents for metal NPs. 3 Thus, several studies have demonstrated the versatility of N-heterocyclic carbene ligands in stabilising and structuring NPs of metals like Ru, 4 Rh, 5 or Pd 6 for significant applications in catalysis, such as the hydrogenation of alkenes and alkynes, the Buchwald–Hartwig amination or the oxidation of alcohols.…”
mentioning
confidence: 99%